(untitled) (Semiárida, 2024)
Controlled deficit irrigation (CDI) intentionally provides less water than needed at various stages of the crop’s growth cycle to impact fruit yield and quality. CDI is commonly employed in viticulture for its influence on phenolic compounds in berries. However, existing studies mainly focus on Mendoza and San Juan, lacking technical data for the NOA region. In this study, we assess the impact of CDI on the yield and enological quality of Malbec and Torrontés Riojano grapes. The research took place in the Antinaco Valley - Los Colorados, La Rioja province, Argentina, from 2018 to 2019, in a commercial vineyard with drip irrigation, vine care, and 20-year-old vines trellis. CDI was applied at 50 % of the water requirement from veraison to harvest, using a completely randomized block design with three repetitions. The study evaluated vine yield, morphometric characteristics, and chemical parameters of the berries and must. Results showed no significant differences in Malbec grape weight and cluster number per plant, except for cluster and berry weight. Torrontés Riojano exhibited no response to CDI in cluster number per plant. Notably, parameters such as berries per cluster, volume, average weight, and diameter differed significantly between the two varieties, with superior results observed without water deficit. Chemical analysis indicated no changes in skins and must, except for total acidity in Malbec grape must. Anthocyanins in Torrontés Riojano grapes significantly increased with CDI. While CDI negatively impacted most morphometric berry parameters, polyphenols in Torrontés Riojano skin and total acidity in Malbec grape must were affected.